Analysis of the Relationships of the Ploidy and Cell Cycle Kinetics to Differentiation and the Female Sex Steroid Hormone Receptors in Adenocarcinoma of the Endometrium. Issue 5 (26th January 2016) - Geisinger, Kim R.; Kute, Timothy E.; Marshall, Richard B.; Homesley, Howard D.; Morgan, Timothy M.
Abstract : Flow cytometry was used to evaluate proliferative activity and ploidy status in 21 endometrial adenocarcinomas. These data were compared with their histologic and nuclear grades and their estrogen and progesterone receptor contents. Proliferative activity was significantly related to histologic and nuclear grades and the progesterone receptor status but not to the estrogen receptor status. Unlike the majority of solid human malignant neoplasms, only seven tumors were aneuploid, the remainder being diploid. Ploidy was not significantly associated with either grading system, receptor status, or the proliferative index.